Pembentukan Undang- Undang Nomor 28 Tahun 2014 Tentang Hak Cipta Analisis Politik Hukum - Rizka Awdina (Lembaga Pengembangan Kinerja Dosen, 2025)
Regulations regarding copyright protection in Indonesia are contained in Law Number 28 of 2014 concerning Copyright which was enacted during the leadership of President Susilo Bambang Yudhoyono. The law is a replacement for Law No. 19 of 2002 concerning Copyright and is a follow-up to Presidential Instruction Number 11 of 2011 which mandates the Ministry of Law and Human Rights to be responsible for economic development specifically in the field of copyright. The author can convey that the character of this legal product is responsive to the fulfillment of community aspirations, both individuals and various social groups, so that it is relatively more capable of reflecting a sense of justice in society compared to the previous Law, namely Law No. 19 of 2002. However, related to the enforcement of the Copyright Law, there are still obstacles, from the law enforcement instruments to the culture in society which basically prioritizes communal values.